Proceedings of the 25th ACM SIGKDD International Conference on Knowledge Discovery &Amp; Data Mining 2019
DOI: 10.1145/3292500.3330774
|View full text |Cite
|
Sign up to set email alerts
|

Blending Noisy Social Media Signals with Traditional Movement Variables to Predict Forced Migration

Abstract: Worldwide displacement due to war and conflict is at all-time high. Unfortunately, determining if, when, and where people will move is a complex problem. This paper proposes integrating both publicly available organic data from social media and newspapers with more traditional indicators of forced migration to determine when and where people will move. We combine movement and organic variables with spatial and temporal variation within different Bayesian models and show the viability of our method using a case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Therefore, it is not surprising that similar trends appear to be emerging when considering the prevalence of misinformation on social media surrounding COVID-19 [1,33,51,55]. While the type of misinformation being studied varies in these studies, all the studies show that misinformation sharing is occurring.…”
Section: Types and Frequency Of Shared Url Contentmentioning
confidence: 87%
See 1 more Smart Citation
“…Therefore, it is not surprising that similar trends appear to be emerging when considering the prevalence of misinformation on social media surrounding COVID-19 [1,33,51,55]. While the type of misinformation being studied varies in these studies, all the studies show that misinformation sharing is occurring.…”
Section: Types and Frequency Of Shared Url Contentmentioning
confidence: 87%
“…Kousy and colleagues [33] used a random sample of tweets containing different coronavirus keywords and hashtags, and found that misinformation and unverifiable content within the tweets was being shared at a high rate, particularly by individual and informal group accounts (33.8%). Researchers have identified a number of conspiracy theories being shared [1,51,55], e.g., linking 5G to COVID-19, but the levels of sharing, the information cascades related to some of these conspiracies, and the belief in the conspiracy vary depending upon the user group studied and the specific conspiracy. [30] analyzed a set of misinformation claims identified by Google Fact Check Explorer and found that 88% of these claims were posted on social media sites, and that most of the information was recontextualization or 'spinning' of factual information.…”
Section: Types and Frequency Of Shared Url Contentmentioning
confidence: 99%
“…For instance, if a conflict occurs in a specific region, this could be accurately measured by identifying users' reactions in that particular location via social media. In recent years, several universities and research centres have been working with big data in forecasting displacement globally, examining social media for sentiment analysis, and in evaluating economic and social variables (European Commission, 2017;Singh et al, 2019). In this sense, an ideal model could include behavioural and sentiment analysis collected online.…”
Section: Necessary Variables To Be Included In the Toolmentioning
confidence: 99%
“…In [5], the authors provide short-term forecasts (two weeks ahead) for movements based on traditional indicators (e.g., socio-demographics) and social media sources such as news, Twitter, and event data. They derive roughly 400 features and use a hierarchical Bayesian model to provide probability densities, as opposed to a point forecast.…”
Section: Figurementioning
confidence: 99%